Business and Human Rights Journal (Cambridge University Press)
It seeks to advance the academic discussion on business and human rights as well as promote concern for human rights in business practice. BHRJ strives for the broadest possible scope, authorship and readership. Its scope encompasses interface of any type of business enterprise with human rights, environmental rights, labour rights and the collective rights of vulnerable groups.
Keywords: Politics